(3QSGFd ShQjG hadSWjf(B: s /((3fjSGf (B1913- (3JTQjf GdChd(B)s - (3CcThQG, jhSas ((3GdTGQbI, GdEeGQGJ,s (3QhGjGJ, s, 2024)
(3jMJhj GdcJGH Ydi KdGKjf QSGdI cJHgG CKfGA RjGQJg Edi ShQjG (B((3HjQhJ(B) (3hadSWjf hGdbOS GdTQja YGe (B1913(3, hfTQgG aj UMjaI zhbJy GdJj JUOQ aj ChQjfHhQZ, eNHkQG GdbqQGA Yf eG QCJ YjfGg aj Jdc GdOjGQ, heG YGjTg ajgG (BThe book contains thirty letters written by the author during his visit to Syria (Beirut), Palestine, and Jerusalem in 1913. He published them in the newspaper "Waqt," which is issued in Orenburg. In these letters, he informs readers about what his eyes witnessed in those regions and the experiences he had there.s
Translated form the original title in Turkish language: Suriye ve Filistin Mektuplari published by Otuken Yayinlari 2022.
Arabic
Keywords: Early 20th century; HN50-995 Social history and conditions. Social problems. Social reform- By region or country; Letters; Travel diary; Turkish historian; Palestine; Syria